Complex equation of maths education in South Africa - Nick Dall (The UNESCO Courier, 2023)
The latest Trends in International Mathematics and Science Study (TIMMS) 2019 confirms what those on the ground have known for decades: South African school students are bad at maths. At primary school level, South Africa had the third lowest score out of the 64 countries. Things are no better at high school, where South Africa’s Grade 9 learners received the second lowest score out of 39 countries. Moreover, less than a third of all students in the final year of high school take maths – and only half of them pass their exams, according to data from the South African Institute of Professional Accountants (Midrand, Greater Johannesburg).